FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR DALAM PEMBERIAN OPINI AUDIT ATAS LAPORAN KEUANGAN (Studi pada Auditor di BPK Perwakilan Provinsi Riau) - Ifany Arfa Unnisa; Nurazlina Nurazlina; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was purpose to aimed the effect of interim investigation, indepedence, skills audit and scope audit on giving audit opinion on finances report. Collecting data of this study using a questionnaire submitted to 55 auditors who work at Badan Pemeriksa Keuangan (BPK) Riau Province Representation. From questionnaires distributed 48 questionnaires (87.27%) ware completed and can be processed. Data analysis methode for this research was multiple regressionwith SPSS version 17. Result of this study give evidence that interim investigation, indepedence and skils audit effect to ward giving audit opinion on finances report. Mean while scope audit didn't effect to ward giving audit opinion on finances report. The results showed that interim investigation have an effect on the giving audit opinion with coefficient of regression equal to 0.022by significance value equal to 0.000 (alpha 0.05). Indepedence have an effect on the giving audit opinion with coefficient of regression equal to 0,042 by significance value equal to 0.000 (alpha 0.05). Audit skills have an affect the on the giving audit opinion with coefficient of regression equal to 0.011 by significance value equal to 0.000 (alpha 0.05) . Audit scope do not affect on the giving audit opinion with coefficient of regression equal to 0.369 by significance value equal to 0.000 (alpha 0.05). R2 square value equal to 0.547 or 54,7% which means that the independent variable in this study could affect the dependent variable, while the rest45,3% is explained by other variables not included in this study.Keywords: audit opinion, interim investigation, indepedence, skills audit, and scope audit.